(untitled) (Altre Modernità, 2013)
Carlo Bertero was trained in Alba and then in Turin, studying with very good teachers who taught him, in addition to botany, political and ethical principles. After having studied the domestic flora, the young botanist travelled to the Antilles (1816-1821), to Chile (1827-1830) and to Tahiti (1830-1831). Thanks to his scientific works many new species were recognized and many specimina were sent to Europe to collectors as well as to botanic gardens, being spread out in different places. When, in 1831, the boat, on which Bertero was boarded, sank into Pacific ocean, all his collection of Tahitian plants disappeared with him. Despite of the dispersion of the collected materials, the botanists have been successful in reconstructing a good part of his activity. Nevertheless his unique writing appeared on the magazine El Mercurio Chileno, when the botanist was living in Santiago during the government of F.A. Pinto, the first liberal president of such country. The historical documentation has disclosed that, during his co-operation with the magazine, the Italian botanist supported the governmental policy, being consistent with his juvenile principles. When Pinto was overthrown, after a fierce civil war, which brought the conservative party to the power, Bertero fell into disgrace and had to leave the country, while the mission to write a natural story of Chile was granted to his competitor, the French botanist Claude Gay, who joined the new political course.